2019
DOI: 10.1002/celc.201900556
|View full text |Cite
|
Sign up to set email alerts
|

Active Anchoring Polysulfides of ZnS‐Decorated Porous Carbon Aerogel for a High‐Performance Lithium‐Sulfur Battery

Abstract: A carbon aerogel composite modified with ZnS (ZnS-CA) was successfully prepared through a simple in situ synthesis and used as a cathode for lithium-sulfur batteries. The nanopore ZnS-CA composites with a high specific surface area and rich mesoporous structure exhibit stronger adsorption and immobilization ability for polysulfides. The ZnS-CA/S cathode materials offer excellent electrochemical performances with lasting cycling stability and high specific capacity. In particular, the 6ZnS-CA/S sample achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, the charge transfer resistance of HCS/S cathode without adding ZnS nanolayer increases significantly in the subsequent middle-frequency region, indicating the difficulty of charge transfer in the battery system. In contrast, the accelerated electrochemical process with ZnS coating could be attributed to the strong chemisorption and catalytic conversion effect to polysulfide that are also reported in other metal sulfur-based cathodes [37,55]. In the low-frequency region, the inclined line is a reflection of the Warburg impedance which relates to the diffusion rate of lithium ions.…”
Section: Resultsmentioning
confidence: 75%
“…However, the charge transfer resistance of HCS/S cathode without adding ZnS nanolayer increases significantly in the subsequent middle-frequency region, indicating the difficulty of charge transfer in the battery system. In contrast, the accelerated electrochemical process with ZnS coating could be attributed to the strong chemisorption and catalytic conversion effect to polysulfide that are also reported in other metal sulfur-based cathodes [37,55]. In the low-frequency region, the inclined line is a reflection of the Warburg impedance which relates to the diffusion rate of lithium ions.…”
Section: Resultsmentioning
confidence: 75%
“…As displayed in Figure 2D , the binding energy for Zn 2p3/2 and 2p1/2 were 1,021.8 and 1,044.8 eV, respectively. ( Hua et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further prove the strong interaction ability between Ag 2 S and Li 2 S n ( n = 4, 6, 8) species, the adsorption energies ( E ads ) of Li 2 S n species on Ag 2 S (022) facet were obtained by DFT calculation. [ 42 ] Figure 8 a shows the most stable constructions of Li 2 S n ( n = 4, 6, 8), and the optimal configurations of Ag 2 S‐absorbed Li 2 S n species were shown in Figure 8b. It can be found that the adsorption energies of Li 2 S 8 , Li 2 S 6 , and Li 2 S 4 on Ag 2 S facet were −5.48, −4.75, and −3.86 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%